Correlation of endometrial morphology by transvaginal sonography with histopathological examination in patients with abnormal uterine bleeding - Srinivasan, Suguna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Abnormal uterine bleeding (AUB) is the most common complaint worldwide. Among Indian women, AUB not only affects the quality of life but also leads to serious consequences such as anemia. prolonged and frequent periods lead to morbidity, diminished quality of life and social embarrassment. Hence this study is undertaken to correlate the endometrial morphology by transvaginal ultrasound with histopathological findings of endometrium in women with AUB. Methods: In this study 173 women suffering from AUB were included. This cross-sectional study was conducted by Transvaginal ultrasound using a 7.5 Mhz Philips Transvaginal sonography (TVS) probe to study endometrial morphology (ET). It is measured at the thickest part in the longitudinal plane and included both endometrial layers. Endometrial sampling and histopathological examination were done. Results: It is observed in our study, AUB is more common among the perimenopausal women (50.9%) and also in multiparous women (86.7%). The commonest problem in our study population is heavy menstrual bleeding (HMB) (45.7%). In our study, the endometrial morphology assessed by TVS correlated statistically with the histopathology of endometrium (p<0.001). Hence, TVS, which is affordable and non–invasive can be used as the first line investigation of AUB, but histopathology of the endometrium always gives the confirmatory result. Conclusions: TVS can be used as the initial investigation for AUB, as it is affordable, non–invasive and has good acceptability by the patients. The endometrial morphology assessed by TVS correlated statistically with histopathological examination.